Methodologies for researching feminisation of agriculture what do they tell us? - Farnworth, Cathy Rozel; Lecoutere, Els; Galiè, Alessandra; Van Campenhout, Bjorn; Elias, Marlène; Ihalainen, Markus; Roeven, Lara; Bharati, Preeti; Valencia, Ana Maria Paez; Crossland, Mary; Vinceti, Barbara; Monterroso, Iliana (International Food Policy Research Institute, 2021)
An increasing body of literature suggests that agriculture is “feminizing” in many low and middle-income countries. Definitions of feminisation of agriculture vary, as do interpretations of what drives the expansion of women’s roles in agriculture over time. Understanding whether, how, and why feminisation of agriculture is occurring, and finding ways to properly understand and document this process, requires effective research methodologies capable of producing nuanced data. This article builds on five research projects that set out to deepen narratives of feminisation of agriculture by empirically exploring the dynamics and impacts of diverse processes of feminisation—or masculinisation—of agriculture on gender relations in agriculture and food systems. To contribute to the development of effective research methodologies, the researchers working on these projects associate the insights they have derived in their empirical research with the methodologies they have used. They reflect on how their methodological innovations enabled them to obtain new, or more nuanced, insights into processes of feminisation of agriculture. A first insight is that the definition of ‘feminisation of agriculture’ is a decisive factor in determining the evidence we produce on the process. Second, the feminisation of agriculture should be understood as a nonlinear continuum. Research methodologies need to be capable of capturing dynamics, complexity, as well as multiple and diverse context—and time—specific drivers. Third, bias in data can arise from gender norms which mediate whether women are acknowledged by wider society as farmers in their own right. Such norms may result in significant underestimations of women’s roles in agriculture. This observation warrants a critical awareness that data used to measure or proxy aspects of feminisation of agriculture may reflect such biases. Finally, some research methodologies can be useful to identify and leverage entry points to support women’s agency and empowerment in processes of feminisation of agriculture.